A pharmacovigilance study on antibody-drug conjugate (ADC)-related neurotoxicity based on the FDA adverse event reporting system (FAERS) - Tang, Linlin; Sun, Cuicui; Liu, Wenshan; Wu, Haiyan; Ding, Chuanhua (Frontiers in Pharmacology, 2024)
Background： Antibody-drug conjugates (ADCs) are a relatively new class of anticancer agents that use monoclonal antibodies to specifically recognize tumour cell surface antigens. However, off-target effects may lead to severe adverse events . This study evaluated the neurotoxicity of ADCs using the FDA Adverse Event Reporting System (FAERS) database.Data were extracted from the FAERS database for 2004 Q1 to 2022 Q4. We analysed the clinical characteristics of ADC-related neurological adverse events (AEs). We used the reporting odds ratio (ROR) and proportional reporting ratio (PRR) for the disproportionality analysis to evaluate the potential association between AEs and ADCs.Results：A total of 562 cases of neurological AEs were attributed to ADCs. The median age was 65 years old ([Min; Max]=3; 92).Neurotoxic signals were detected in patients receiving brentuximab vedotin, enfortumab vedotin, polatuzumab vedotin, trastuzumab emtansine, gemtuzumab ozogamicin, inotuzumab ozogamicin, and trastuzumab deruxtecan. The payloads of brentuximab vedotin, enfortumab vedotin, polatuzumab vedotin, and trastuzumab emtansine were microtubule polymerization inhibitors, which are more likely to develop neurotoxicity. We also found that brentuximab vedotin-and gemtuzumab ozogamicin-related neurological AEs were more likely to result in serious outcomes. The eight most common ADC-related nervous system AE signals were peripheral neuropathy (ROR(95 % CI)=16. 98(14.94-19.30), PRR(95 % CI)=16.0(14.21-18.09) ), cerebral haemorrhage (ROR(95 % CI)=9.45( 7.01-12.73), PRR(95 % CI) = 9.32(6.95-12.50) ), peripheral sensory neuropathy (ROR(95 % CI)= 47.87 (33.13-69.19), PRR(95 % CI) =47. 43(32.93-68.30) ), polyneuropathy (ROR(95 % CI )= 26.01 (18.61-36.33), PRR(95 % CI)=25. 75(18.50-35.86)), encephalopathy (ROR(95 % CI)= 5.16(3.32-8.01), PRR(95 % CI)=5.14(3.32-7.96)), progressive multifocal leukoencephalopathy (ROR(95 % CI)= 22.67(14.05-36.58), PRR(95 % CI)=22.52(14.01-36.21)), taste disorder ( ROR(95 % CI)= 26. 09(15.92-42.76), PRR(95 % CI) =25.78(15.83-42.00)), and guillain barrier syndrome (ROR(95 % CI)= 17. 844(10.11-31.51), PRR(95 % CI)=17. 79(10.09-31.35)). The mortality rate appeared to be relatively high concomitantly with AEs in the central nervous system.ADCs may increase the risk of neurotoxicity in cancer patients, leading to serious mortality. With the widespread application of newly launched ADC drugs, combining the FAERS data with other data sources is crucial for monitoring the neurotoxicity of ADCs. Further studies on the potential mechanisms and preventive measures for ADC-related neurotoxicity are necessary.